2015
DOI: 10.1159/000437301
|View full text |Cite
|
Sign up to set email alerts
|

Novel Prokinetic Acotiamide Reduces Transient Lower Esophageal Sphincter Relaxation in Healthy Subjects

Abstract: Background/Aims: Currently, there is no study evaluating the effect of acotiamide on transient lower esophageal sphincter relaxations (TLESRs). The aim of this study was to evaluate the effect of acotiamide on TLESRs using simultaneous high-resolution manometry (HRM) and impedance-pH monitoring. Methods: Ten healthy subjects were enrolled. On day 1, subjects underwent HRM and impedance-pH recordings as a baseline. Subjects ate a 750-kcal liquid meal; recording was continued for 2 h while the subjects were in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…18 However, it has been reported that acotiamide has no apparent effect on esophageal movement in healthy people or GERD patients. 19,20 On the other hand, it has been reported that acotiamide reduced regurgitation with transient lower esophageal sphincter relaxation (TLESR) and improved esophageal clearance in healthy subjects, 38 and it ameliorated minor esophageal peristaltic abnormalities observed in healthy subjects. 39 In a recent report on acotiamide, Yamashita et al 40 Abbreviations: NS, not significant; SD, standard deviation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 However, it has been reported that acotiamide has no apparent effect on esophageal movement in healthy people or GERD patients. 19,20 On the other hand, it has been reported that acotiamide reduced regurgitation with transient lower esophageal sphincter relaxation (TLESR) and improved esophageal clearance in healthy subjects, 38 and it ameliorated minor esophageal peristaltic abnormalities observed in healthy subjects. 39 In a recent report on acotiamide, Yamashita et al 40 Abbreviations: NS, not significant; SD, standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…The primary cause of GERD is thought to be esophageal motility dysfunction accompanied by weak esoph-ity and GERD has not been sufficiently investigated, and at present there is no consensus regarding these fields. On the other hand, it has been reported that acotiamide reduced regurgitation with transient lower esophageal sphincter relaxation (TLESR) and improved esophageal clearance in healthy subjects,38 and it ameliorated minor esophageal peristaltic abnormalities observed in healthy subjects 39. Acotiamide inhibits AChE, a catabolic enzyme of ACh, and also antagonizes muscarine M 1 and M 2 receptors, which exist on nerve endings.…”
mentioning
confidence: 99%
“…It was observed that acotiamide can reduce TLESRs and enhancing esophageal bolus clearance in healthy subjects. 64 These observed effects would be favorable for treating patients with GERD and future research is needed.…”
Section: Medical Treatment Optionsmentioning
confidence: 99%
“…Among them, TLESRs are considered to play a major role in provoking reflux [10]. Although several drugs, including γ-aminobutyric acid type B receptor agonists, histamine H2 receptor antagonists (nizatidine) [11], prokinetic agents (acotiamide [12], itopride [13]), atropine [14,15], and morphine [16], have been found to inhibit TLESRs in humans, these have not been used for GERD in clinical practice owing to their effects on the central nervous system or a lack of their efficacy in treating GERD. However, TLESRs are still an attractive target for the treatment of GERD.…”
Section: Introductionmentioning
confidence: 99%